Therapy refractory menorrhagia as first manifestation of Hermansky-Pudlak syndrome - Lohse, J.; Gehrisch, S.; Tauer, J. T.; Knöfler, R. (Hämostaseologie, 2011)
Introduction Oculocutaneous albinism (OCA) in combination with a platelet function defect caused by a disturbed release reaction from platelet δ-granules (storage pool defect – SPD) is typical for the autosomal recessive inherited Hermansky-Pudlak syndrome (HPS).Case report A girl (age: 13 years) with OCA was hospitalized with transfusion-requiring menorrhagia. The suspicion of HPS was confirmed by results of lumi-aggregometry. Suspecting a disorder in primary haemostasis treatment with tranexamic acid (10 mg/kg body weight every 8 h i. v.), desmopressin (0.3 μg/kg body weight every 8 to 12 h) and hormonal therapy (norethisterone) was started but the menorrhagia persisted. Clinical response was finally achieved by a single injection of 100 μg/kg body weight recombinant factor VIIa (rFVIIa).Conclusion The diagnosis of HPS should be suspected in patients with OCA and bleeding symptoms and is confirmed by the proof of SPD. In case of absent clinical response to desmopressin the application of rFVIIa should be considered. Hormones and antifibrinolytics are useful options in the treatment of extensive menorrhagia.
Keywords: Hermansky-Pudlak syndrome; menorrhagia; desmopressin; rFVIIa